2016
DOI: 10.1159/000443433
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Visfatin Ameliorated Diabetic Nephropathy in Type 2 Diabetic Mice

Abstract: Background/Aims: Visfatin is a known adipokine which may improve insulin resistance in obesity and have an anti-diabetic effect via the insulin receptor. We studied the effects of visfatin on diabetic nephropathy in type 2 diabetic mice. Methods: Diabetic male db/db mice were treated with intraperitoneal injections of visfatin. Basal parameters were measured in all mice and glucose tolerance test (GTT) and insulin tolerance test (ITT) were performed in diabetic mice. The histopathological and molecular changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…El Samahi et al [26] have demonstrated reduced visfatin level in diabetic patients with microalbuminuria and suggested that visfatin plays a role in the pathogenesis of diabetic nephropathy. A recent experimental study has shown that visfatin administration ameliorated diabetic nephropathy in type 2 diabetic mice and concluded that visfatin has a protects against diabetic nephropathy [27]. In the present study, visfatin levels were significantly increased diabetic nephropathy cases compared to those without nephropathy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…El Samahi et al [26] have demonstrated reduced visfatin level in diabetic patients with microalbuminuria and suggested that visfatin plays a role in the pathogenesis of diabetic nephropathy. A recent experimental study has shown that visfatin administration ameliorated diabetic nephropathy in type 2 diabetic mice and concluded that visfatin has a protects against diabetic nephropathy [27]. In the present study, visfatin levels were significantly increased diabetic nephropathy cases compared to those without nephropathy.…”
Section: Discussionsupporting
confidence: 58%
“…Yilmaz et al [15] have reported a positive association of visfatin with insulin resistance and degree of albuminuria in type 2 diabetic patients. Experimental studies have shown that chronic administration of visfatin ameliorated nephropathy in experimental type 2 diabetic mice [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, calcium dobesilate eliminates oxygen (hydroxyl) radicals and inhibits the inflammatory response ( 15 ), reducing the levels of inflammatory cytokines. Moreover, calcium dobesilate can effectively stabilize capillary endothelial cells, reduce endothelial cell rupture ( 16 ), improve lymphatic return and other functions ( 17 ), inhibit secretion and synthesis of aldose reductase ( 18 ), and decrease the levels of sorbitol ( 19 , 20 ), effectively regulating the levels of BDNF and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on its role in the development of insulin resistance provided inconsistent results. In obese patients, increased visfatin levels, similarly to increased adiponectin levels, may play a protective role [99,100]. In a study by Kang et al, [100] on diabetic db/db mice it was shown that visfatin might have a protective effect in diabetic nephropathy without the hypoglycemic effect.…”
Section: Obesity Adipokines and Chronic Complicationsmentioning
confidence: 99%